Characterization of Flavonols Present in Barks and Needles of Pinus wallichiana and Pinus roxburghii - NAEEM*, ISMAT; TASKEEN, ABIDA; MUBEEN, HIFSA; MAIMOONA, ALYA (Asian Journal of Chemistry, 2024)
Flavonoids are a diverse group of natural products found in all plants. In present study five flavonols namely quecetin, kampherol, rhamnetin, isorhamnetin and myrcetin were identified and estimated in Pinus roxburghii and Pinus wallichiana bark and needles extracts in different solvents. Study was carried out on acid hydrolyzed methanolic extracts which was further fractionated into diethyl ether, n-butanol, ethyl acetate and water extracts. Quercetin was found to be the most abundant flavonol present in Pinus wallichiana and Pinus roxburghii barks and needles. Myrcetin was not present in Pinus wallichiana needles while. rhamnetin was only present in Pinus wallichiana bark.